2007
DOI: 10.1007/s11095-006-9187-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cyclic Phosphate Prodrug Approach for Cytochrome P450-activated Drugs Containing an Alcohol Functionality

Abstract: Since CYP enzymes reside predominantly in the liver and secondarily in the small intestine, the results indicate that cyclic phosphate prodrugs represent a very feasible liver- or intestinal-targeted drug delivery strategy for drug molecules containing an alcohol functionality. This may potentially improve the efficacy and the safety profile of the alcoholic parent drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…15 2-Chloro-1,3,2-dioxaphosphorinane 2-oxide was synthesized by reacting phosphorus oxychloride with 1,3-propanediol as described in the literatures. 17,18 Methylphosphonic dichloride, methyl methylphosphonochloridate, and phenyl methyl phosphinyl chloride were prepared by adapting the synthesis methods mentioned in our previous work. 19 Synthesis of Organo-Phosphorus Flame Retardants (FRs).…”
Section: Methodsmentioning
confidence: 99%
“…15 2-Chloro-1,3,2-dioxaphosphorinane 2-oxide was synthesized by reacting phosphorus oxychloride with 1,3-propanediol as described in the literatures. 17,18 Methylphosphonic dichloride, methyl methylphosphonochloridate, and phenyl methyl phosphinyl chloride were prepared by adapting the synthesis methods mentioned in our previous work. 19 Synthesis of Organo-Phosphorus Flame Retardants (FRs).…”
Section: Methodsmentioning
confidence: 99%
“…1 We have recently reported that cyclic phosphates could serve as potential cytochrome P450 (CYP) 3A4-selective prodrugs of drug molecules having a free hydroxyl group. 10 To date, this prodrug approach has been successfully applied to 18βglycyrrhetinic acid to gain antiulcer and anti-inflammatory sustained-release effects. 11 Bioconversion of cyclic phosphate prodrugs have been designed to undergo an initial CYPcatalyzed oxidation at the C4 methine primarily by CYP3A forms (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the enzymes that are traditionally used for activation are unspecific esterases, 3 alkaline phosphateses, 4 peptidases 5 and specific cytochrome P450s. 6,7 Nitroreductases (NTRs) are a relatively new class of enzyme in the area of prodrug activation. 8,9 Unlike traditional enzymes, which activate mostly carrier-linked prodrugs (drug with promoiety), NTRs are involved in the activation of bioprecursor prodrugs, which are transformed by direct reduction or reduction followed by elimination to the active agent.…”
mentioning
confidence: 99%